Analisis Pengaruh Job Satisfaction dan Transformational Leadership Terhadap Employee Performance Melalui Organizational Commitment - Magdhalena, Elizabeth; Tanuwijaya, Justine; Gunawan, Andreas Wahyu (https://jurnal.binamandiri.ac.id/, 2023)
The purpose of this research is to analyze the effect of job satisfaction and transformational leadership on employee performance with organizational commitment as a mediation variable. The population of this research is medical and non-medical personnel at West Jakarta Private Hospital. The method that will be used for taking the sampling is saturate sample. The number of samples that were used on this research was 104 respondents. The method of data analyst that was used with Structural Equation modeling (SEM). The result of this research shows that job satisfaction was not influenced by organizational commitment of medical personnel and non-medical of Private Hospital West Jakarta. Job satisfaction and transformational leadership effected job performance of medical personnel and non-medical of Private Hospital West Jakarta with straight or throughout organizational commitment as mediation. Transformational leadership has a positive effect for organizational commitment of Medical Personnel and non-medical personnel of Private Hospital West Jakarta.